Dialogue with what? The Socratic way on names in the Cratylus and the possibility of dialectics as a research method - Acuña, Leonardo Rodríguez (2024)
In this essay, based on an interpretation of the Cratylus, I defend that Plato conceives the mediation of ordinary language as necessary for the dialectical investigation of reality. In the discussion about the rightness of names, Socrates maintains a compatibilist position between Conventionalism and Naturalism that allows him to judge the imperfection in the establishment of names. Such reconstruction allows us to conceive both the criticism of etymology as a research method, and the dialectics as an overcoming method. The dialectician, to be successful, must consider the necessary imperfection of our names.